The Effect of Addition of Antioxidant to The Stability of Green Tea Water Extract As Anti Acne - SaibÃƒÂ‚Ã‚Â , Nadya Fadila (Indonesian Journal of Cancer Chemoprevention, 2010)
There are so many potential effects that green tea, such as antibacterial activity against Propionibacterium acnes, that caused acne. In the previous study, green tea had been made in gel. In this study, formulaÃÂ  of green tea water extract gel is developed with addition of antioxidantÃÂ  so that stability of the gelÃÂ  would increase. Gel of green tea water extract were made using Carbopol 940 with glycerin as the solvent. The chosen antioxidant was sodium sulfite. It is also combined with chelating agent, EDTA (Edetic Acid). The activity of green tea water extract gel was determined and tetracycline HCl gel was used as the reference. The addition of sodium sulfite 1% w/w into gel with Carbopol 940 1% w/w as the base prevent the change of color in more than eight weeks. Minimum Inhibitory Concentration (MIC) of green tea water extract without either sodium sulfite or EDTA was 1.20 ÃÂ± 0.11 cm against Propionibacterium acne. MIC of green tea water extract with addition of sodium sulfite 1% w/w was 1.19 ÃÂ± 0.28 cm. MIC of green tea water extract with addition of sodium sulfite 1% w/w and EDTA 0.1% w/w was 1.25 ÃÂ± 0.22 cm. The addition of sodium sulfite 1% w/w caused viscosity of gel decrease 42.1%. The addition of sodium sulfite 1% w/w increased the color stability of green tea water extract. The addition of sodium sulfite 1% w/w didnÃ¢â¬â¢t decrease its antibacterial activity against Propionibacterium acnes.